ARBUSCULAR MYCORRHIZAL Glomus versiforme INDUCED BIOPROTECTION OF APPLE TREE AGAINST SCAR SKIN DISEASE - Shoujun Yang; Zhonglan Zhang; Zhifen Zhang; Shuyi Shi (Acta Scientiarum Polonorum: Hortorum Cultus, 2014)
Apple scar skin viroid (ASSVd) is a serious pathogen of apple fruits that results in severe loss in apple production. Up to nowadays, many ASSVd management options are applied to resist the disease, but the diserable resulits are not achieved. Therefore, this study was conducted in 2010–2012 at experimental field of Penglai City, Shandong Province, China (E 120°57’22’’, N 370°38’33’’) to investigate whether arbuscular mycorrhizal (AM) Glomus versiforme protects Red Fuji apple trees (Malus × domestica Borkh) against apple scar skin viroid. Red Fuji apple trees were inoculated with Glomus versiforme and then potential protection mechanism was explored and compared to noninoculated plants. The results showed that inoculation with Glomus versiforme significantly increased root length colonization rate and clearly decreased the percentage of disease severity of apple scar skin disease. Compared to non-inoculated plants, Glomus versiforme obviously enhanced total nitrogen and phosphorus concentrations in leaves. Root colonization by Glomus versiforme induced an increase in defense-related enzyme activities in fruits, such as the enhanced activities of catalase, ascorbate peroxidase, chitinase and glucanase. Significant differences in acid content of fruit and fruit yield were observed as apple roots were colonized by Glomus versiforme. It is therefore concluded that Glomus versiforme can be regarded as a biocontrol agent to protect apple trees against the infection with ASSVd.